Integrasi Google Sites dalam model PjBL dan kemampuan bernalar terhadap keterampilan menulis esai siswa SMA - Hartati, Restiana Dwi; Setiawan, Budhi; Suhita, Raheni (Universitas Mulawarman, 2025)
This study aims to investigate the influence of implementing the Project-Based Learning (PjBL) model in combination with the Google Sites platform on students’ essay writing skills, while taking into account their level of reasoning ability. The study was prompted by the observation that many students continue to face challenges in producing coherent, logical, and argumentative essays in the context of Indonesian language learning. Adopting a quasi-experimental design with a 2×2 factorial model, the research involved 66 students from SMA Negeri 10 Samarinda and MA Negeri 2 Samarinda during the 2024/2025 academic year. Data were obtained through objective tests to assess reasoning ability and performance-based assessments to evaluate essay writing skills. The findings reveal that the integration of the PjBL model with Google Sites exerts a significant positive effect on students’ essay writing performance. Moreover, reasoning ability was found to significantly influence outcomes, with students demonstrating higher reasoning skills achieving superior writing results. An interaction effect between the applied learning model and students’ reasoning ability was also identified, indicating a combined impact on essay writing performance. These results underscore the potential of integrating project-based learning with digital technologies as an effective strategy for enhancing students’ writing competence in language education.